The clinical impact of chronic liver disease in patients undergoing transcatheter and surgical aortic valve replacement: Systematic analysis of the 2011–2017 US hospital database. Issue 7 (25th September 2021) - Lee, David Uihwan; Han, John; Fan, Gregory Hongyuan; Hastie, David Jeffrey; Kwon, Jean; Lee, Ki Jung; Addonizio, Elyse Ann; Karagozian, Raffi
Abstract: Objectives: In this study, we use a national database to evaluate post‐transcatheter (TAVR)/surgical aortic valve replacement (SAVR) outcomes stratified using chronic liver disease (CLD). Background: In patients undergoing TAVR and SAVR, the surgical risks should be optimized; this includes evaluating hepatic diseases that may pose an operative risk. Methods: 2011–2017 National Inpatient Sample was used to select in‐hospital TAVR and SAVR cases, which were stratified according to CLD (cirrhosis, hepatitis B/C, alcoholic/fatty/nonspecific liver disease). The cases–controls were matched using propensity score matching and compared with various endpoints. Result: After matching for demographics and comorbidities, for TAVR, 606 and 1818 were with or without CLD; for SAVR, 1353 and 4059 were with and without CLD. In TAVR, there was no differences in mortality (2.81% vs. 2.75% OR 1.02 95% CI 0.58–1.78) or length of stay (6.29 vs. 6.44d p = 0.29), and CLD‐present patients had marginally increased costs (228, 415 vs. 226, 682 p = 0.048). There were no differences in complications. In multivariate, there was no difference in mortality (aOR 1.02 95% CI 0.58–1.79). In SAVR, CLD patients had higher mortality (7.98% vs. 3.23% OR 2.60 95% CI 2.00–3.38), length of stay (13.3 vs. 11.3 days p < 0.001), and costs (273, 487 vs. 238, 097 p < 0.001). CLD patients also had increased respiratory failure (9.02% vs. 7.19% OR 1.28 95% CI 1.03–1.59) and bleeding (8.43% vs. 6.33% OR 1.36 95% CI 1.08–1.71). In multivariate, CLD had higher mortality (aOR 2.60 95% CI 2.00–3.38). Conclusion: CLD is associated with higher mortality and complications in patients undergoing SAVR; however, no correlation was found in patients undergoing TAVR.